The governance of policy reforms in southern Europe and Ireland: social dialogue actors and institutions in times of crisis (Geneva, 2014)
"This edited volume provides an overview of the changes that have occurred in industrial relations systems in southern Europe and Ireland as a result of the debt crisis and subsequent fiscal consolidation policies. The authors take stock of developments and consider policy implications. They identify the new challenges in today's crisis context and rapidly changing economic environment, offering a range of strategies and actions aimed at reinforcing social dialogue and industrial relations institutions in ways compatible with international labour standards and the ILO Decent Work Agenda."